Analisis Komparasi Sentimen Positif Pada Media Sosial Dan Pemberitaan Brand Kecantikan Somethinc - Ridha Fatima Azzahra (Lembaga Pengembangan Kinerja Dosen, 2024)
The Indonesian beauty industry has experienced remarkable growth in recent years, positioning the country as a lucrative market for businesses operating in the beauty tech sector. This rapid expansion has fueled fierce competition, prompting many manufacturers to adopt digital marketing campaign strategies to attract consumers and boost sales. Amidst this dynamic landscape, Somethinc, a leading beauty tech brand, has achieved remarkable success, multiplying its sales by 14 times compared to the previous year and securing the top spot as the best-selling brand on e-commerce platforms with total sales of Rp 53.2 billion. In light of this competitive environment, media monitoring plays a crucial role in understanding the positive sentiment surrounding Somethinc across social media and online news platforms. This study employs a qualitative descriptive method, utilizing a netnographic approach and leveraging media monitoring analytical tools to gather data through the Brand24 application. The primary objective of this research is to identify the dominant sources of positive sentiment for Somethinc across social media and news platforms. Comparative analysis of positive sentiment, mentions, reach, and product discussions on social media and news platforms regarding Somethinc reveals a notable advantage in social media mentions.